Social Effects of Online Game Addiction in Adolescents: A Systematic Review - Agrista Yudistira Purnama; Elizabeth Risha Murlina Lema; Brigita Maria Karouw; Hilwatus Saadah; Stefanus Evan Rafael; Ah Yusuf (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to determine the social effects of online game addiction in adolescents and increase our knowledge of adolescents who experience online game addiction. This was a systematic review of the literature using the Scopus, Science Direct and SAGE Journals databases during five years with a randomized controlled trial. All the studies included online game addiction, focusing on the effect of social influence on online gaming addiction in adolescents. Based on the findings of 15 research articles used showed that there was a social influence on online gaming addiction experienced by adolescents. Social constraints proved to be an essential factor in the excessive internet use of adolescents. Other findings showed that associated internet gaming disorders and a lack of attention suggests that individualistic cultural orientations exacerbate these relationships without gender differences